2022
DOI: 10.3390/app12178665
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Microwave Sensor for Characterization and Adulteration Detection in Edible Oil

Abstract: A low-cost microwave sensor was designed for oil adulteration detection and characterization of pure edible oil using dielectric spectroscopy. The sensor’s final design was fabricated on a low cost 1.6 mm thick FR-4 substrate with a combination of a complementary split ring resonator and a transmission line. The sensor’s dimensions were 35 × 30 × 1.6 mm3 with a substrate dielectric constant of 4.3. A 5.25 GHz resonance frequency was selected as a reference for characterization and adulteration detection in pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The selected operating frequency in the study [33] is also similar with the proposed one, but the size of the sensing system in this study is lower than the sensor in [33]. Beside this, due to the higher wavelength, the proposed study will be affected less with respect to the studies [25,34,35].…”
Section: Proposed Sensor Design and Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The selected operating frequency in the study [33] is also similar with the proposed one, but the size of the sensing system in this study is lower than the sensor in [33]. Beside this, due to the higher wavelength, the proposed study will be affected less with respect to the studies [25,34,35].…”
Section: Proposed Sensor Design and Resultsmentioning
confidence: 93%
“…The drawback of this study is very high resonance frequency which can be affected by any circumference changes and results in abnormal shifts. Characterization and adulteration detection in edible oil has been performed by using microwave sensor [25]. In the study, the resonance frequency, bandwidth, and resonance shift are 5.25 GHz, 180 MHz, and 200 MHz, respectively.…”
Section: Proposed Sensor Design and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mai et al has demonstrated a 3D structure to reflect one handedness of circularly polarized light and absorbing the opposite handedness [58]. Moreover, to avoid the complex fabrication procedures, few works reported on single layer structures to design meta-mirror [59][60]. To the best of our knowledge, all the reported works on meta-mirrors either have fabrication complexities or low reflection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable interest has been sparked into renewable energy because of the increasing demand for energy [1][2][3][4][5][6][7][8]. These resources have the potential to furnish the modern energy demands while retaining features of cost-effectiveness and minimal negative environmental impact [9][10][11][12][13][14][15]. One of the most promising candidates of renewable energy is the solar energy, which can be transformed into heat, electricity, and photochemical reactions from continuous solar irradiation [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%